2023
DOI: 10.3390/educsci13070679
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Teachers’ Demographics on Total Quality Management Parameters—The Case of Primary Education

Abstract: The purpose of this paper is to highlight the application of TQM in primary education (PE) by exploring teachers’ views and, more specifically, by examining the impact of their demographic data on their attitude towards TQM. A study was conducted among teachers in Greek public primary schools with the aim being to investigate their views on seven TQM parameters. The study used a structured questionnaire that was positively evaluated for validity and reliability. In total, 2088 completed questionnaires were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
1
1
0
2
Order By: Relevance
“…Notably, the age distribution indicates a considerable concentration in the 60 and above age group, suggesting a potential demographic shift or longevity in Special Education Teaching careers. These findings align with the study of Kaiseroglou (2023) which concluded that there is a need for targeted strategies to support and retain experienced educators.…”
Section: Profile Of the Respondentssupporting
confidence: 86%
“…Notably, the age distribution indicates a considerable concentration in the 60 and above age group, suggesting a potential demographic shift or longevity in Special Education Teaching careers. These findings align with the study of Kaiseroglou (2023) which concluded that there is a need for targeted strategies to support and retain experienced educators.…”
Section: Profile Of the Respondentssupporting
confidence: 86%
“…It could educate and empower employees to be part of the environmental solution, thereby enriching their job experience and aligning their personal values with corporate objectives. This strategic integration could result in a workforce that is not only more efficient and environmentally conscious but also more motivated and committed, driving forward the company's sustainability agenda and competitive edge [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Produktivitas Indonesia hanya sebesar 1,37%, hampir empat kali lebih rendah daripada produktivitas Thailand yang mencapai 5,28%. Nilai produksi Indonesia juga lebih rendah jika dibandingkan dengan Vietnam (4,39%) dan Malaysia (2,16%) (Kaiseroglou et al, 2023).…”
Section: Hasil Dan Diskusi Urgensi Manajemen Pendidikan Tinggi Dalam ...unclassified
“…Beberapa penelitian menunjukkan hasil yang tidak konsisten terkait keberhasilan implementasi prinsip TQM dalam pendidikan tinggi (Al Kadri et al, 2023). Sebaliknya, studi lain juga menunjukkan bahwa nilai-nilai TQM dapat diterapkan secara efektif dalam pendidikan tinggi dan sesuai dengan nilai-nilai pendidikan tinggi (Hosang et al, 2021;Kaiseroglou et al, 2023;.…”
Section: Faktor Penghambat Dan Pendukung Dalam Implementasi Tqm Dalam...unclassified